Games in coalitional form - Ehud Kalai (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2007)
How should a coalition of cooperating players allocate payoþs to its members? This question arises in a broad range of situations and evokes an equally broad range of issues. For example, it raises technical issues in accounting, if the players are divisions of a corporation, but involves issues of social justice when the context is how people behave in society. Despite the breadth of possible applications, coalitional game theory oþers a uni.ed framework and solutions for addressing such questions. This brief survey presents some of its major models and proposed solutions.
Keywords: 330; Kooperatives Spiel; Koalition; Theorie